Adaptasi dan Validasi Awal Alat Ukur Sikap Membuang Sampah Sembarangan (Littering Attitude Scale) ke dalam Versi Bahasa Indonesia - Muliadi, Rahmad; Jatnika, Ratna; Hanami, Yuliana (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
Litter is one of the most important environmental problems to be addressed. Because the problem is very complex, the efforts made must be comprehensive and involve many parties. Several researchers stated that public attitudes towards the phenomenon of littering itself are important to study, because it can be one of the factors that determine whether someone will litter or not. By following the guidelines of the International Test Commission, this study aims to translate and adapt into Indonesian the "littering attitude scale" so that it can be used in Indonesia. The results of this study present the process of obtaining two pieces of validity evidence, namely evidence based on test content that obtained from expert assessments, and validity evidence based on response process that explored through how some participants understand the meaning of the scale elements. Specifically, the two pieces of validity evidence obtained can be the initial basis for this scale to be tested on a larger sample. In general, this study is expected to be a guide for the initial process of adaptation or development of a psychological scale.